Data supporting: 'Investigating professional values among pilots, cabin crew, ground staff, and managers to develop aviation safety management systems' - Chan, Wesley Tsz-Kin; Li, Wen-Chin (Cranfield University, 2022)
This dataset includes survey responses from N=317 participants, on levels-of-agreement with conceptualisations of cultural dimensions. Professional culture (occupational background) was the independent variable for the cited article. In the dataset, professional culture is under the @4Groups variable, representing pilots (1); cabin crew (2); ground staff (3); airline managers (4).
Keywords: aviation'; 'culture'; 'profession'; 'occupation'